New significant advances of regional geological survey in the blank regions of Qinghai-Xizang Plateau - Gangyi, Zhai (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.136-7